Does chronic ankle instability affect side-cutting in female soccer players? - Takeuchi, Shiki; Anan, Masaya (International Journal of Sports Medicine, 2024)
Lateral ankle sprains have a high recurrence rate, often developing into chronic ankle instability (CAI). CAI affects movement strategy during side-cutting maneuvers, with inconsistent results in many studies. This study aimed to clarify the characteristics of movement strategies during side-cutting maneuvers in female soccer players with and without CAI. Thirteen female soccer players with CAI and twelve healthy controls performed 10 successful trials of side-cutting maneuvers in three directions (anterolateral, lateral, and posterolateral) under unanticipated conditions. Compared to the control group, the CAI group displayed an increased stance time in the lateral and posterolateral side-cutting maneuvers (lateral: p=0.021, effect size=0.97, posterolateral: p=0.014, effect size=1.00). In posterolateral side-cutting maneuvers, the CAI group displayed a decreased posterior ground reaction force at 19–30% and 42–54% of the entire stance phase compared with the control group (p=0.001, effect size=1.30–1.42). Female soccer players with CAI may display increased stance time to compensate for self-reported ankle instability and may also exhibit decreased braking and propulsive force when side-cutting to sharper angles. These observations suggest a hypothesis that could help in the assessment of cutting maneuvers under unanticipated conditions after ankle sprains.
Keywords: lateral ankle sprain; anticipation; cutting maneuvers; movement strategies; chronic ankle instability